2001
DOI: 10.1029/2001ja000031
|View full text |Cite
|
Sign up to set email alerts
|

Auroral electron distributions derived from combined UV and X‐ray emissions

Abstract: Abstract. The Polar Ionospheric X-ray Imaging Experiment and the Ultraviolet Imager on board the Polar satellite provide the first simultaneous global scale views of the electron precipitation over a wide range of electron energies. By combining the results from these two remote sensing techniques we have developed a method to derive the electron energy distributions that reproduce the true electron spectra from I to 100 keV and that can be used to calculate the energy flux in the energy range from 100 eV to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 24 publications
0
42
0
Order By: Relevance
“…The X rays measured by PIXIE are produced by electrons from ∼3 keV to 100 keV. Detailed descriptions of the data processing from PIXIE is given by Østgaard et al [1999] and details on deriving four‐parameter electron spectra from PIXIE measurements are given by Østgaard et al [2000] and Østgaard et al [2001].…”
Section: Instrumentation and Data Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…The X rays measured by PIXIE are produced by electrons from ∼3 keV to 100 keV. Detailed descriptions of the data processing from PIXIE is given by Østgaard et al [1999] and details on deriving four‐parameter electron spectra from PIXIE measurements are given by Østgaard et al [2000] and Østgaard et al [2001].…”
Section: Instrumentation and Data Processingmentioning
confidence: 99%
“…By combining the measurements from UVI and PIXIE it is possible to derive 5 min‐average electron distributions from 100 eV to 100 keV with a spatial resolution of ∼700 km in the Northern Hemisphere when Polar is at 6–8 R E . A validation of the method by comparing with directly measured electron spectra by low‐altitude satellites is given by Østgaard et al [2001]. The time resolution of 15 min (5 min‐average every 15 min) is determined by the duty cycling of the front chamber of PIXIE and the spatial resolution is basically determined by the pinhole size of the PIXIE instrument.…”
Section: Instrumentation and Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of com-parison studies exist in the literature (e.g. Basu and Jasperse, 1987;Vondrak et al, 1988;Senior, 1991;Watermann et al, 1993;Doe et al, 1997;Germany et al, 1997;Dymond et al, 2001;Østgaard et al, 2001). Such studies are complicated when the stochastical processes operate on different scales.…”
Section: Introductionmentioning
confidence: 99%
“…During the recovery phase, PIXIE showed a precipitation maximum in the morning sector which was not seen by UVI. Many studies have reported such a maximum in the energetic electron precipitation in the dawn region, including substorm studies (Jelly and Brice, 1967;Berkey et al, 1974;Østgaard et al, 2001;Aksnes et al, 2002) and statistical studies involving different geomagnetic conditions (Hartz and Brice, 1967;McDiarmid et al, 1975;Wallis and Budzinski, 1981;Spiro et al, 1982;Hardy et al, 1985;Hardy et al, 1987). Østgaard et al (1999) used models of the gradient and curvature drift of electrons to estimate the energy of eastward drifting electrons causing the X-rays seen by PIXIE.…”
Section: Introductionmentioning
confidence: 99%